Evaluating the impact of tooth carving training on the knowledge, attitude, and practice of general dental practitioners in clinical practice - Vidya G. Doddawad; KP Poornima; Suhani Jain; S Shivananda; CJ Sanjay; BC Sulochanadevi (Journal of Education and Health Promotion)
BACKGROUND: Tooth carving exercises using wax blocks are integral in Indian dental education, aiding in the understanding of dental anatomy and enhancing manual dexterity. This study evaluates the impact of tooth carving training on the knowledge, attitude, and practice of dental practitioners in clinical settings. MATERIALS AND METHODS: A questionnaire-based, descriptive study was conducted among dental practitioners in Karnataka, India, who had completed preclinical tooth carving exercises in their BDS curriculum. Data collection included demographic information and a self-administered questionnaire with 38 multiple-choice questions assessing knowledge, attitude, and practice. A total of 349 responses were collected out of 400 distributed, yielding a 70% response rate. Statistical analysis was performed using SPSS version 23, employing descriptive and inferential statistics. RESULTS: The majority of respondents were in the 41-50 age group, with a balanced gender distribution. Most held a Master of Dental Surgery (MDS) degree, and the majority had over 15 years of clinical practice. The study revealed a positive perception of tooth carving exercises, with respondents recognizing their value in dental education as well as in their clinical practice. CONCLUSION: Tooth carving exercises remain effective for learning tooth anatomy, as indicated by positive responses from dental practitioners. The study advocates for the continued inclusion of tooth carving in the undergraduate dental syllabus while recognizing the potential for incorporating innovative teaching methods for enhanced learning experiences.